Solutions and Associated Costs for the Development of River Crossing Infrastructure in the Lower Danube Region: Array - Dragomir, Ștefan; Dragomir, Georgeta (Journal of Danubian Studies and Research, 2020)
The paper presents several system for crossing the river and an originally solution that no necessity expensive costs to built. The maintenances costs are very low. The results are related to the dynamic characteristics of the crossing systems, because each of them necessity a lot of technically solutions. Because of their size and the nature of the crossed obstacles, these types of structures can offer easy access outside and inside for inspection maintenance works, but comparing with bridges. In time these crossing systems are exposed to a variety of phenomena which can cause them damage but the intervention modality for repair the damages it is not so costly.